(3GdOQ GdefXhe (B((3OjhGf(B)s - (3YHO Gddg Hf YHO GdSdGe GdCfOdSjs
(3ChdgG (B:s
(3cJH Edi UOjb dg jTcQg Ydi Lejd HdZg Yfg hQZHI aj GdehOI ajg GdBf EPG Qhi GdSdh XeGFj hCUGH HYOce GdCSGI OhGFj s
(3BNQgG (B:s
(3bhdg(B: (3dh de jcf ddegQLGf MdjI JYWdG s
(3cGf GdeDda MjkG SfI (B393 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3JhHfLf (B(229) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdCOHs